2002
DOI: 10.1002/jcla.10038
|View full text |Cite
|
Sign up to set email alerts
|

Decorin transfection in human mesangial cells downregulates genes playing a role in the progression of fibrosis

Abstract: The proteoglycan decorin inhibits TGF-beta; therefore, it could antagonize progression of fibrotic diseases associated with activation of TGF-beta(1). The effect of decorin transfection in human mesangial cells (HMCs) on the expression of genes related to kidney fibrosis was investigated. HMCs, isolated from glomeruli of healthy portions of human kidneys removed due to carcinoma, were histochemically typed. Decorin cDNA cloned in a eukaryotic expression vector was transfected into HMCs. Gene expression of fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 30 publications
(31 reference statements)
2
15
0
Order By: Relevance
“…Our data support this possibility, as we observed that TGF-β 1 protein levels and the ratio of pSmad2,3 to Smad2,3 (index of TGF-β 1 activity) were decreased in the Ad-decorin group, as compared to diabetic-controls. The other possibility is decorin can inhibit the expression of TGF-β 1 mRNA, which has been confirmed in other studies [23,24]. Our results are also consistent with these studies.…”
Section: Discussionsupporting
confidence: 82%
“…Our data support this possibility, as we observed that TGF-β 1 protein levels and the ratio of pSmad2,3 to Smad2,3 (index of TGF-β 1 activity) were decreased in the Ad-decorin group, as compared to diabetic-controls. The other possibility is decorin can inhibit the expression of TGF-β 1 mRNA, which has been confirmed in other studies [23,24]. Our results are also consistent with these studies.…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, decorin is involved in normal tissue development and differentiation (Riquelme et al, 2001). Decorin activity also can regulate proteins associated with extracellular-matrix formation (Dudas et al, 2001;Costacurta et al, 2002). Dermatopontin competes with decorin for TGFB binding and also interacts with collagen directly (Kuroda et al, 1999;Okamoto et al, 1999).…”
Section: Discussionmentioning
confidence: 98%
“…It has been shown that as a result of this interaction, decorin can inhibit as well as activate TGF-␤-dependent signaling depending on the cell type (12,37). It inhibits TGF-␤-dependent signaling in mesangial cells (38), glioma cells (39), and differentiated myotubes (30) and stimulates this signaling in osteoblasts (16) and non-differentiated myoblasts (18). Several proteoglycans have a well established role as co-receptors (19,40).…”
Section: Discussionmentioning
confidence: 99%